Design of a beamforming antenna sensor for environmental noise detection to discriminate vehicle emission according to road conditions. (October 2022) - Djungha Okitadiowo, John P.; Lay-Ekuakille, A.; Isernia, T.; Massaro, A.
Abstract: The noise instance is unpleasant in the ears and leads to harmful or even dramatic consequences, and we all have this obligation to limit the extent of noise in a consistent way in our cities. It is very important and even crucial to underline that noise pollution has a negative impact on human health and activities, so this harmful environmental pollution coming from different sources must be seriously monitored with dedicated equipment that are able to discriminate, categorise and even give or display the noise level in terms of dB. From this, the antenna sensor, specifically oriented or dedicated for the detection of the quality and quantity of noise pollution, can be realized by using a sensor array. In this paper we propose a design and simulation of a Beamforming based antenna sensor to detect the direction of arrival (DOA) of the noise and how to differentiate between different noises that are in a single signal envelope. The system has the ability to record and store the noise for further processing. From the signals (noise) we can deduce other events that are happening that are invisible to us, when these signals are processed, they reveal the hidden realities; the proposal of this Beamforming antenna and its system associated with algorithms can make the difference of a noise of a vehicle driving on a good road and on a destroyed one. This can bring many benefits for the protection of the environment, especially in the pollution, see also on the financial point, maintenance of the road and other.